PWE-061A Differentiating ibd and ibs using faecal calprotectin testing: an audit of optimal cut-off points. (17th June 2017) - Adamson, M; Loehry, J
Abstract : Introduction: Faecal Calprotectin testing is a relatively new diagnostic test. It is recommended by NICE (2013) but noted that optimal cut off points require more evidence to enhance the clinical decisions being made. This study reports on the results received in a hospital laboratory during a nine month period, the patient's following tests and diagnosis, and how this will inform and impact upon the current guidelines for practice. Method: The Biochemistry department reported a total of 1113 orginal Calprotectin Tests performed between the period of nine months. This was sent in the form of a database. Each of these patients left in the database were assessed to see if they were referred to the Gastroenterology or Colorectal team in the hospital and then if they were, whether they went onto having a scope. If this did occur the result was documented. Results: Conclusion: Looking at the results we can see some very striking patterns indicating that a positive Faecal Calprotectin Stool Test is an effective demonstrator of likely IBD. The data can also be interpreted to show that all parties are aware of this fact and are responding accordingly. The key points are: Calprotectin tests are an effective demonstrator of likely IBD. Measuring levels allows avoidance of unnecessary diagnostic interventions making it cost effective. Highly raised Calprotectin results (1001–1800) can be justification for going straight to test, avoiding a unnecessary clinic appointments, as potentially 80%+ will have IBD. Unless symptoms are acute, in which case a stool MC and S should also be performed to rule out infectious causes. Reference ranges and guidance currently used needs rising as low calprotectin levels rarely lead to IBD diagnosis References: . NICE, 2013. Faecal calprotectin tests for inflammatory disease of the bowel [online]. Available from: https://www.nice.org.uk/guidance/dg11. [Accessed: 27/07/2016]. . Patient.info, 2014. Irritable bowel syndrome [online]. Available from: http://patient.info/pdf/2854.pdf . The IBS network, 2016. What is IBD? [online]. Available from: https://www.theibsnetwork.org/have-i-got-ibs/what-is-ibs/. [Accessed: 27/07/2016]. Disclosure of Interest: None Declared